Age‐induced mitochondrial DNA point mutations are inadequate to alter metabolic homeostasis in response to nutrient challenge. Issue 11 (13th October 2020) - Moore, Timothy M.; Zhou, Zhenqi; Strumwasser, Alexander R.; Cohn, Whitaker; Lin, Amanda J.; Cory, Kevin; Whitney, Kate; Ho, Theodore; Ho, Timothy; Lee, Joseph L.; Rucker, Daniel H.; Hoang, Austin N.; et al.
Abstract: Mitochondrial dysfunction is frequently associated with impairment in metabolic homeostasis and insulin action, and is thought to underlie cellular aging. However, it is unclear whether mitochondrial dysfunction is a cause or consequence of insulin resistance in humans. To determine the impact of intrinsic mitochondrial dysfunction on metabolism and insulin action, we performed comprehensive metabolic phenotyping of the polymerase gamma (PolG) D257A "mutator" mouse, a model known to accumulate supraphysiological mitochondrial DNA (mtDNA) point mutations. We utilized the heterozygous PolG mutator mouse (PolG +/mut ) because it accumulates mtDNA point mutations ~ 500‐fold > wild‐type mice (WT), but fails to develop an overt progeria phenotype, unlike PolG mut/mut animals. To determine whether mtDNA point mutations induce metabolic dysfunction, we examined male PolG +/mut mice at 6 and 12 months of age during normal chow feeding, after 24‐hr starvation, and following high‐fat diet (HFD) feeding. No marked differences were observed in glucose homeostasis, adiposity, protein/gene markers of metabolism, or oxygen consumption in muscle between WT and PolG +/mut mice during any of the conditions or ages studied. However, proteomic analyses performed on isolated mitochondria from 12‐month‐old PolG +/mut mouse muscle revealed alterations in the expression of mitochondrial ribosomal proteins, electron transport chain components, and oxidative stress‐related factors compared with WT. These findings suggest that mtDNA point mutations at levels observed in mammalian aging are insufficient to disrupt metabolic homeostasis and insulin action in male mice. Abstract : Mice harboring supraphysiological mtDNA point mutations (PolG +/mut ) respond similarly to WT animals during metabolic challenge including nutrient excess, starvation, and acute exercise.